Serological Screening and Risk Factors Associated with Leishmania infantum Positivity in Newly Diagnosed HIV Patients in Greece - Chrysa Voyiatzaki; Apollon Dareios Zare Chormizi; Maria E. Tsoumani; Antonia Efstathiou; Konstantinos Konstantinidis; Georgios Chrysos; Aikaterini Argyraki; Vasileios Papastamopoulos; Effie G. Papageorgiou; Marika Kotsianopoulou (Microorganisms, 2024)
A serological screening was conducted to detect IgG antibodies against Leishmania infantum (L. infantum) in newly diagnosed human immunodeficiency virus (HIV) patients in Greece. The study also examined potential risk factors and the agreement of commercially available serological methods. IgG antibodies against L. infantum were detected using enzyme-linked immunosorbent assay (ELISA), indirect immunofluorescence antibody test (IFAT), and Western blot (WB). Out of 155 samples, 14 (9.0%) tested positive for IgG antibodies against L. infantum using at least two methods. Statistical analysis showed substantial agreement between WB and IFAT methods (Cohen’s kappa = 0.75) but moderate overall agreement among the three methods (Fleiss’ kappa = 0.42). Additionally, HIV+ intravenous drug users faced 3.55 times (p = 0.025) higher risk of testing positive for L. infantum IgG, positing that anthroponotic transmission between these patients is a plausible hypothesis based on existing literature. Non-invasive and cost-effective techniques are preferred to detect asymptomatic infections, and leishmaniasis screening should be conducted immediately after HIV diagnosis in endemic regions to enable prophylactic treatment for leishmaniasis in addition to antiretroviral therapy. To maximize sensitivity, performing at least two different serological methods for each patient is recommended.